Development of an effective protocol for in vitro multiplication of peppermint (Mentha piperita) - SHARMA, MANMOHAN; SHARMA, MAMTA; SALGOTRA, R K; GUPTA, MEHAK; SINGH, ANJANI K; GUPTA, L M (The Indian Journal of Agricultural Sciences, 2019)
Mentha piperita is a completely sterile hybrid due to the fact that male organs of flower fail to develop. The stamens remain abnormally short, sometimes degenerate and wither from bud. As a result it is not amenable to improvement by sexual crosses. Ruthless exploitation of peppermint due to growing interest in the commercialization of plant based medicines has lead to drastic decrease of natural resource base which will result in extinction. In order to meet pharmaceutical needs and to provent the plants from extinction, development of rapid large scale propagation systems is a necessity. In vitro multiplication was carried out for mass production of disease free planting material without seasonal constraints ensuring germplasm conservation and sustainable use of the medicinal crop.